Rubiparvus bistigma, a new genus and species of Empoascini (Hemiptera, Cicadellidae, Typhlocybinae), with a checklist of the Alebroides group in Chinese fauna - Xu, Ye; Wang, Yu-Ru; Lu, Si-Han; Dietrich, Christopher H.; Qin, Dao-Zheng (Zootaxa, 2016)
A new leafhopper genus of the tribe Empoascini, Rubiparvus gen. nov., is described based on Rubiparvus bistigma sp. nov. from Yunnan (southwest China). Habitus photos and illustrations of male genitalia of this new species are given. Differences between the new genus and closely related genera are discussed. A checklist of the Alebroides generic group in the Chinese fauna is provided.